Assessment of Primary Healthcare Accessibility of the Three Health Insurance Systems - สายรัตน์ นิ่มอนงค์ (Journal of Health Science of Thailand, 2023)
The objective of this study was to assess primary health care accessibility among three health insurance systems in Thailand, which included Universal Coverage Scheme (UCS), Social Security Scheme (SSS) and Civil Servant Medical Benefit Scheme (CSMBS). It was conducted by evaluating the aspects of planning and access of benefits of each primary health care system relating to Primary Health Care Act 2019 and the Announcement of Primary Health Care System Board on Primary Health Care Services 2020 in order to investigate the patterns of services and the quantitative data of services in each system and to determine policy recommendations for further improvement of the primary health care system. Mixed method was utilyzed in this research including the collection of qualitative data from the documents related to management and payment mechanism and the quantitative reports. The receiving service information was divided into three parts: (1) outpatient services of three health insurance systems; (2) primary care services of CSMBS and SSS, which form reimbursement database consisted of outpatient services, health promotion and disease prevention, mid-term care and long-term care; and (3) primary care services of USC, which were collected from the National Health Security Office Annual Report 2021 consisting of outpatient services, health promotion and prevention, mid-term and long-term care, as well as HIV prevention. The results showed that all 3 schemes were different in payment mechanism and did not cover all services specified by the health care systems board 2020. Also, the outpatient services of each were different: the patients under UCS received the services as 3.44 times/person/year followed by CSMBS and SSS with 2.88 and 2.49 times/person/year, respectively. It could be recommended for the mid-term suggestion that the Administrator of Primary Care Office of the Ministrty of Public Health should coordinate with government purchasers to determine the goal of valued primary care system and be the core organization joining with other related organizations to develop the information standards of primary care services as well as define the health outcomes for employing value-based payment and improving effectiveness of primary health care services.